Islam and Economic Development: By Muhammad Umer Chapra, The International Institute of Islamic Thought and Islamic Research Institute, Islamabad, Pakistan, 1993, 166 pp. (American Journal of Islam and Society, 1994)
Islam and Economic Development is another intellectual contributionby M. Umer Chapra, a well-known Muslim social scientist and author ofToward a Just Monetary System and Islam and the Economic Challenge.He has been devoting time, energy, and experience to the cause of Islamizationof knowledge, and this work, which shares much in theme, tone,and territory with his earlier works, reflects his deep commitment anddedication to a painstaking task. This thought-provoking book, whichoffers a global and integrative perspective of the phenomenon of developmentwithin the framework of an Islamic worldview, is divided into sixchapters, preceded by the author’s preface and a foreword by Zafar IshaqAnsari, and followed by notes and refelences, a bibliography, and anindex.Chapter 1, “The Kind of Development,” initiates the discussion of thebook’s general theme by presenting the issue of development in terms ofgoals and the strategies employed to realize those goals. The two basicgoals-efficiency and equity-are defined within the Islamic concept ofjust development, which is derived from the concepts of tawW (theoneness and unity of God), khikifah (the vicegerency of human beings), and 'adalah (justice)The terms “efficiency” and “equity,” as defined on page 8, needfurther explanation, especially when the authm has discussed the importantanalytical issue of the optimality and the maximization of the twovariables. Moreover, the concept of khilafah (state) and the two basicgoals that it seeks to achieve, ‘adalah (justice) and falah (general well-being),could have been better linked to the time basic pillars of Islam:tawhid, risalah (prophethood), and dkhirah (the hereafter).Chaptet 2, ”Can Secularism Foster Just Development?,” features developmentstmtegies of the two prominent secular systems: the freemarket system and the socialist system. Chapra points out that thereallocation of nsources cannot be realized within the value-neutralframework of secular systems. He notes that the ftee market system,which is based on the concept of self-intenst, cannot motivate people toact in the interest of society. He shows the futility of the Swirling pattern ...